Evaluación maderable del bosque de la comunidad campesina Alto Perillo con fines de aprovechamiento sostenido en Contamana Loreto, Perú - 2021 - Sangama Shuña, Andres (2022)
The study was carried out in the forest of the Alto Perillo peasant community for sustainable use in Contamana Loreto, Peru. The objectives were to record the floristic composition of commercial species with diameter ? 40 cm; determine the IVI; define the volume of standing commercial timber and the economic valuation. The population. The study area was in total (ha): 5 102.36 (ha) of the forests of the Alto Perillo peasant community in Contamana Loreto, Peru. We worked with a sample of 500.00 (ha). The methodology used to do the field work was the design of a random inventory. 33 commercial species were found, distributed in 15 botanical families. The largest number of species is in the Fabaceae botanical family, Myristicaceae. The abundance of commercial species is in the Fabaceae family, which represents 22.67% and 16.27% of the total species registered in the forest inventory of the study area; The dominance of the commercial species is 1687.83 m2. The most frequent species are "machimango, sapotillo". The representative species, according to the IVI are, "Coto callana, machimango, aguano cumala, mashonaste, shihuahuaco, sapotillo, cumala, copaiba and lupuna". The volume of commercial wood is 39.04 m3 / ha. The species with the highest Valuation per hectare is the Callana preserve with S /. 364.69 soles.